A dictionary of statistics / Graham J G Upton; Ian Cook - Upton, Graham J. G.
This wide-ranging dictionary covers over 2,300 statistical terms in accessible, jargon-free language. All existing entries and web links have been revised and updated to ensure that the content is as relevant as possible. An indispensable reference work for any students or professionals who come into contact with statistics at work or university.